Do Public Smoking Bans have an Impact on Active Smoking? Evidence from the UK. (6th November 2013) - Jones, Andrew M.; Laporte, Audrey; Rice, Nigel; Zucchelli, Eugenio
Abstract The literature on the effects of public smoking bans on smoking behaviour presents conflicting results and there is limited evidence on their impact on active smoking. This paper evaluates the impact of smoking bans on active smoking using data from the British Household Panel Survey and exploiting the policy experiment provided by the differential timing of the introduction of the bans in Scotland and England. We assess the short‐term impact of the smoking bans by employing a series of flexible difference‐in‐differences fixed effects panel data models. We find that the introduction of the public smoking bans in England and Scotland had limited short‐run effects on both smoking prevalence and the total level of smoking. Although we identify significant differences in trends in smoking consumption across the survey period by population sub‐groups, we find insufficient evidence to conclude that these were affected by the introduction of the smoking bans. These results challenge those found in the public health literature but are in line with the most recent strand of economic literature indicating that there is no firm evidence on the effects of smoking bans on smoking. Copyright © 2013 John Wiley & Sons, Ltd.